Considerações sobre o agramatismo: traçados e tropeços - Tumiate, Cláudia Fernanda (2007)
This study focuses on and discusses the concept of agrammatism which names and qualifies a particular kind of aphasic symptom related to a specific damaged cerebral zone or area. Physicians, speech pathologists/therapists and linguists have tried to describe such a linguistic occurrence also endeavored to develop theoretical proposals in order to provide plausible explanations for the mentioned phenomenon. My interest in discussing the so called agrammatism started at the very beginning of my clinical practice as a speech therapist, i.e., when I received one of my first aphasic patients. The effects of that patient s utterances on me were quite paradoxical in the sense that, although evaluated as severely ungrammatical, they sounded communicative to me, that is, I felt at ease to interpret them. Face-to-face with such a disturbing situation, I decided to study and reflect upon the effects of agrammatical utterances on the listener and also on agrammatism itself. I found out that none of the representative theoretical or descriptive approaches investigated could either help me understand the above mentioned subjective effects, or touch the heterogeneity of the agrammatical utterances . Moreover, I could verify that although not coincident on discursive grounds, most of the investigated theoretical proposals converged as to the methodological-descriptive approach they applied. Two different historical constructs concerning Aphasia are presented in the first part of this thesis: one which was derived from Chomsky s reflections on language and another one which was developed from Jakobson s studies on aphasia. Two researcher s discussions were respectively at stake: Grodzinsky s (1990) and Fonseca s (1995, 2002), respectively. On the second part I aimed at opposing the notions of agrammatism and ungrammaticality which seemed to be a possible source of theoretical-methodological problems. It must be stressed that such a discussion, although recognized by me as extremely important and original on intuitive grounds, has just been initiated. The LAEL-CNPq certified Research Group: Language Acquisition, Language Pathology and Language Clinic, supervised by Dr. Maria Francisca Lier-DeVitto, provides this study with specific theoretical background